CRITICAL HIGHER ORDER THINKING MENURUT FILSAFAT PROGRESIVISME DI KALANGAN MAHASISWA - Maradita, Yolanda; Celine Dian Giroth; Metha Putri Paraswati; Soneta Veronika Saogo; Putrie Beatrix Nelly Amalo (Sanjiwani: Jurnal Filsafat, 2026)
In the world of education a student is required to be able to think critically and systematically, by connecting the philosophy of Progressivism in the world of Christian Religious Education which affects the cognitive improvement of students in reasoning something. Therefore, this generation whose technological developments are increasingly sophisticated, students should be prepared to face the challenges of the times to come. With the aim of research so that students in "Critical Higher Order Thinking" CHOT according to philosophy by utilizing technological developments. In this study the authors used a qualitative method with a descriptive approach. With the results of the discussion regarding the relationship between CHOT and the philosophy of progressivism can help encourage students to think critically about the information received. Thus it is important for students to improve their quality by honing soft skills that are indispensable in the digital era and the world of education.